The Relationship Between Instagram Social Media Use and Mental Health of Adolescent Females at Rajawali Health Vocational School - Rike, Kethryn Keflin; Sitompul, Monalisa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Adolescents experience a number of social, emotional, and physical changes that can affect their mental health. Everyone, especially adolescents, can now easily access and use social media thanks to recent technological advances. One of the most widely used social networking sites among young people is Instagram. Concerns about the impact of social media use on their mental health have arisen as a result of this situation. This study aims to identify the level of Instagram social media use and the level of mental health of adolescent girls and analyze the relationship between Instagram social media use and their mental health. The method used was a quantitative approach with a cross-sectional associative design. The study sample used was 212 students. The results showed that the majority of female students at Rajawali Health Vocational School actively use Instagram social media, with usage levels ranging from moderate to high. This indicates that Instagram has become an important part of adolescent girls' social activities. Most female students have a high level of mental health, which reflects their ability to adapt to social environments and academic pressures. The level of Instagram social media use and mental health are positively and significantly correlated. Using Instagram wisely and moderately can improve psychological health by enhancing social skills and self-confidence. The conclusion is that the majority of students at Rajawali Health Vocational School have good mental health, and there is a positive and significant correlation between the use of Instagram social media and the mental health of adolescent girls.